Joint Online Learning and Decision-making via Dual Mirror Descent - Lobos, Alfonso; Grigas, Paul; Wen, Zheng (2021 International Conference on Machine Learning, 2021)
We consider an online revenue maximization problem over a finite time horizon subject to lower and upper bounds on cost. At each period, an agent receives a context vector sampled i.i.d. from an unknown distribution and needs to make a decision adaptively. The revenue and cost functions depend on the context vector as well as some fixed but possibly unknown parameter vector to be learned. We propose a novel offline benchmark and a new algorithm that mixes an online dual mirror descent scheme with a generic parameter learning process. When the parameter vector is known, we demonstrate an O([T]) regret result as well an O([T]) bound on the possible constraint violations. When the parameter is not known and must be learned, we demonstrate that the regret and constraint violations are the sums of the previous O([T]) terms plus terms that directly depend on the convergence of the learning process.